2006
DOI: 10.1158/1078-0432.ccr-05-2767
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6, a Nuclear Factor-κB Target, Predicts Resistance to Docetaxel in Hormone-Independent Prostate Cancer and Nuclear Factor-κB Inhibition by PS-1145 Enhances Docetaxel Antitumor Activity

Abstract: Purpose: To investigate whether nuclear factor nB (NF-nB)/interleukin 6 (IL-6) was linked to docetaxel response in human prostate cancer cell lines, and whether inhibition of NF-nB sensitized tumor cells to docetaxel. We also aimed to correlate IL-6 (as a surrogate marker of NF-nB) and docetaxel response in hormone-independent prostate cancer (HIPC) patients. Experimental Design: Hormone-dependent (LNCaP) and hormone-independent (PC-3 and DU-145) prostate cancer cell lines were exposed to docetaxel alone or co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
96
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(105 citation statements)
references
References 25 publications
(30 reference statements)
7
96
2
Order By: Relevance
“…The comparison of pre-and posttreatment samples showed increased expression of cytokines regulated by the NF-kB pathway. These data are in concordance with our results showing an increased expression in treated tumors of NF-kB subunits and NF-kB-regulated cytokines, such as IL-6, adding support to a body of evidence on the involvement of this pathway in resistance to chemotherapy in prostate cancer (11). On the other hand, NF-kB activation may induce EMT in prostate cancer (34).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The comparison of pre-and posttreatment samples showed increased expression of cytokines regulated by the NF-kB pathway. These data are in concordance with our results showing an increased expression in treated tumors of NF-kB subunits and NF-kB-regulated cytokines, such as IL-6, adding support to a body of evidence on the involvement of this pathway in resistance to chemotherapy in prostate cancer (11). On the other hand, NF-kB activation may induce EMT in prostate cancer (34).…”
Section: Discussionsupporting
confidence: 93%
“…9, 10). Previous work by our group and others correlated the activation of NF-kB/interleukin (IL)-6 pathways with docetaxel resistance in CRPC models and in patients (11)(12)(13). Other studies support a role of JUN/AP-1, SNAI1, and NOTCH2/Hedgehog signaling pathways in the development of resistance to docetaxel or paclitaxel (14,15).…”
Section: Introductionmentioning
confidence: 80%
“…In addition, basal NF-jB activity is often increased in various types of human cancers, which causes chemotherapy resistance (31). Under certain conditions, cytotoxic drugs, such as taxanes, induce NF-jB activation in different types of malignant cells (26,(32)(33)(34)(35)(36). The present data also showed that docetaxel induced NFjB activation and then upregulated antiapoptotic factors in two ATC cell lines, FRO and KTC-2.…”
Section: Discussionsupporting
confidence: 61%
“…IL-6 is well known as a key downstream target of NF-kB (37). Recently, it was reported that resistance to docetaxel is mediated by increased IL-6 production via NF-kB activation in prostate cancer (38). In addition, it was also reported that autocrine IL-6 production correlates with NF-kB activation in chronic lymphocytic leukemia (CCL) and high IL-6 level is associated with poor prognosis in CCL patients (39).…”
Section: Discussionmentioning
confidence: 99%